(untitled) (SCI-TECH LENS, 2026)
This study assesses waste management systems and their impact on environmental sustainability, emphasizing the role of scientific research, sustainable technologies, biotechnology, public health, and environmental policies. Findings indicate that effective waste management practices reduce pollution, mitigate climate change, protect public health, and support sustainable development. However, challenges such as inadequate infrastructure, weak policy implementation, and limited public participation continue to hinder environmental sustainability in the Philippines and Southeast Asia.